1995
DOI: 10.7863/jum.1995.14.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Peak systolic velocity and flow volume increase with blood pressure in low resistance systems.

Abstract: This study demonstrates that when vascular resistance is low, peak systolic velocity and peak flow volume increase with increasing blood pressure. We used ischemia with reactive hyperemia to create reproducible low resistance conditions in 32 volunteers. Ischemia resulted in sharp increases in systolic and diastolic velocities, while the difference between these velocities increased minimally. Spontaneous variations in subject's systolic blood pressure were positively correlated with peak sys-R ecent reports h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…35 A correlation between the Doppler power and Hct was deter-mined in another study. 37, 38 In the dogs in our study, systemic blood pressure was not evaluated prior to Doppler ultrasonographic examination. In some dogs included in the present study, RBC count, Hct, and hemoglobin concentration were at the lower limit of the reference range or even mildly decreased, but significant associations of these variables with MCL, FA, or CWFA of pre-and postcontrast power Doppler ultrasonography were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…35 A correlation between the Doppler power and Hct was deter-mined in another study. 37, 38 In the dogs in our study, systemic blood pressure was not evaluated prior to Doppler ultrasonographic examination. In some dogs included in the present study, RBC count, Hct, and hemoglobin concentration were at the lower limit of the reference range or even mildly decreased, but significant associations of these variables with MCL, FA, or CWFA of pre-and postcontrast power Doppler ultrasonography were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…In flaccid conditions, the bladder wall arteries have a spiral form [1,2] and it can be assumed that the stretching of the coiled arteries upon distension of the bladder wall, and possible vasoconstriction, accelerate blood circulation purely mechanically. In this context, the investigations of Terry et al [13,14] are particularly relevant; they showed that at least in vessels with low resistance, if there is no change in RI, a rise in PSBFV also represents a rise in the blood flow rate. The flow spectra deduced from the bladder wall vessels showed evidence of low resistance.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the conversion between Doppler shift frequency and velocity requires an accurate Doppler angle correction, which can be hazardous in curved stenotic vessels. Secondly, frequency shifts and velocities may vary with blood pressure [13]. Thirdly, the use of short pulse duration and/or wide Doppler aperture with linear array probes may induce a so-called intrinsic spectral broadening responsible for inaccurate calculations [4,14]; therefore, care and prudence are required in clinical practice [4].…”
Section: Quantification Of Stenosesmentioning
confidence: 99%